Criminal Law Enforcement Against Illegal Sand Mining in the Disaster-Prone Area of the Merapi Mountain Special Region of Yogyakarta - Tuson Dwi Haryanto (Universitas PGRI Madiun, 2024)
This study aims to identify and analyze the efforts of police investigators and civil servant investigators in enforcing criminal law against illegal sand mining in the Mount Merapi Disaster-Prone Area, Yogyakarta Special Region. This study also aims to analyze and direct the possibility of criminal law regulation against illegal sand mining in the future. This study employed normative empirical research method, research that uses primary data and secondary data. Primary data were obtained by interview and documentation, while secondary data were obtained from primary, secondary, and tertiary legal materials. The obtained data were analyzed using a legal approach and a conceptual approach. The following are the findings of this research. First, the Criminal Procedure Code formally guides the enforcement of criminal law by policy investigators and civil servant investigators against illegal sand mining, while Law No.4 of 2009 concerning Mineral and Coal Mining formally guides the enforcement of criminal law by police investigators and civil servant investigators against illegal sand mining. Second, in Chapter XXIII Articles 158-165 of Law No.4 of 2009 regulating Mineral and Coal Mining, criminal laws connected to mining without a permit or illegally are specified. However, the existing provisions require a review related to criminalization, the criminal responsibility system, the pattern of types of criminal sanctions, the pattern of the duration of the crime, and the pattern of criminal formulation, which must synergize with the purpose of punishment. Thus, criminal law enforcement in the mining sector in the future can run effectively.